Influence of 2D:4D ratio on fitness parameters and accumulated training load in elite youth soccer players - Hadi Nobari; Ana Ruivo Alves; Filipe Manuel Clemente; Jorge Pérez-Gómez (BMC, 2021)
Abstract Background Digit ratio (2D:4D) characterized by the length of the second digit (2D) divided by the length of the fourth digit (4D), is a powerful marker of athletic performance. Some studies showed a negative correlation between 2D:4D ratio and sports performances. Objectives The purpose of the present study was three-fold: (1) to analyze the influence of anthropometric and 2D:4D ratio on variations of accumulated training load (ATL) and fitness parameters: maximal oxygen uptake (V̇O2max), countermovement jump (CMJ), isometric muscular strength of the knee extensor for hamstring (ISH) and flexor for quadriceps (ISQ) muscles; along three stages of evaluation of soccer players based on playing positions; (2) to analyze the correlations between 2D:4D ratio and aforementioned parameters; and (3) to investigate if variance in fitness levels and ATL can explain the 2D:4D ratio. Methods Twenty-four elite players under 17 years were daily monitored for their rating perceived exertion and ATL across 24 weeks over the season. Soccer players have also measured in three stages for anthropometric traits and fitness parameters. Results Significant differences were observed between playing positions for body mass, goalkeepers had higher body mass compared to centre-midfielder and winger players. Moreover, there were significant differences in ATL between early-season to mid-season in goalkeepers (P = 0.032). The 2D:4D ratio (left and right) shown largely and negatively association with muscular strength (ISQ: r =  − 0.80; r =  − 0.78, P ≤ 0.001, ISH: r =  − 0.63; r =  − 0.62, P = 0.001, respectively) and VO2max changes (r =  − 0.55, P = 0.005; r =  − 0.50, P = 0.013, respectively); lastly, both 2D:4D ratio significantly predicted changes in muscular strength and VO2max in young soccer players. Conclusions Goalkeepers tended to have higher body mass compared to centre-midfielder and winger players; and 2D:4D ratio revealed a mighty predictor of physical fitness changes in soccer players. Evidence should be helpful to professionals to highlight the usefulness of the 2D:4D into the identification of talent, but also to optimize young players' performance.